Islamization of Knowledge of Ismail Raji Faruqi: Integration-Interconnection to the Contextualization of Indonesian Science - Syihabuddin, Muhammad; Manggala, Kayan; Mustofa, M. Lutfi (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2023)
This article discusses the concept of Islamization of knowledge promoted by Ismail Raji Faruqi. This concept aims to defeat secularism that blinds Muslims and brings misfortune. The spread of secularism has encouraged Muslims to make concessions to what the West offers them. Therefore, reading the Islamization of knowledge in the context of scientific integration-interconnection becomes essential to raise awareness among Muslims who are considered to glorify secular science so that people are too far from the concept of tawhid (monotheism). This research used a literature review method through several textual sources related to the topic discussed, primarily Faruqi's work entitled "Islamization of Knowledge," and secondary in the form of similar articles on the theme of Islamization of knowledge. Then, it is to consider the aims and objectives of the Islamization of knowledge, linking it with the concept of integration-interconnection, and considering the contextualization of the Islamization of knowledge in the Indonesian science. The results of this paper are as follows: Islamization of knowledge becomes an inclusive concept if we consider the existence of two disciplines. As a Muslim scientist, the realm of Islamization of knowledge must be imprinted in him to achieve the ideals of Islam. Islamization of knowledge is closely related to integration-interconnection, namely integrating sciences without legitimizing that one science with another cannot be merged. Islamization of knowledge is also a step in creating an Islamic civilization in the world of science. In the context of Indonesia, the Islamization of knowledge can be seen in the concept of science integration in several Islamic universities in Indonesia which has different concepts, but the same essence. The purpose of Faruqi's thought is to demand Muslims to be creative.